MEANING OF LIFE IN THE MODERN CONCEPT OF POLITICS - Bakutis, Romualdas (Politologija, 2014)
The study examines the place of meaning of life in the modern concept of politics. Although the predominant view nowadays in Western society outlines that meaning of life is a private matter and any wish to solve it would lead to totalitarian consequences, this research contests such position by, firstly, showing that every political theory at its core is guided by a necessity to resolve the problem of nihilism and, secondly, tracing the revolutions of theological and political thinking, which explain why modern political theorists and politicians do not talk about meaning of life. The research consists of two parts. The core thesis of the first one states that meaning of life is the point of exit for every political theory and order because if political thought wants to prove that it is right, it must justify why its proposed order of things is necessary. This can be done only by proving that political thought reflects the purpose of human life which actually is meaning of life. If a political body or political philosophy cannot prove this, it will always be possible to reject their arguments by stating that they are meaningless to humans. At least theoretically such harmony between meanings of human and state existence was achieved by pre-modern Greeks, Romans and Medieval Christendom. In ancient Greek and Christian philosophy it was perceived that the material world is grounded by some metaphysical entity which gives every being on this side certain place and purpose. Therefore, if political philosophy wanted to understand how societies must be governed, thinkers, firstly, would need to find what place for men was conceived by higher entities in otherworldly dimensions. However, this concept was problematic because sooner or later it should have been realized that humans cannot comprehend God’s perfection. Therefore, the concept of God is equal to the concept of nonexistence and such type of metaphysical entity could not give a purpose to the world. Furthermore, after the fall of finalistic worldview it was impossible to prove the old political order and, hence, new search for the meaning of life in the political order began. Essential role by trying to reunite meaning of life and politics was performed by scientific worldview. Science enabled the reconstruction of meaning of life by 2 aspects: firstly, it changed the finalistic understanding of the world by causal and, therefore, it granted a possibility by manipulating cause and effect to recreate every social and natural order. Secondly, after theologians established God as nonbeing, scientists gave a way to provide a frame to the world. Moreover, some of them even envisaged the trend of progress in historical processes which paved a way to fulfil the ultimate purposes of humanity, therefore, meaning of life not in another but in this world. This created conditions for the idea that society should be permanently improved and the ultimate goal of such improvement is the salvation of every individual in this world. Although supporters of liberalism and socialism have a different understanding of this final stage of human development, both of them aim not at preparing individual for the salvation in another reality but they think that ideas of the heaven should be established in this world.